Development of student worksheets with react strategy to facilitate students' mathematical literacy skills in an islamic context - Ramdani Miftah; Dedek Kustiawati; Iftitah Ridhoilahi (AXIOM : Jurnal Pendidikan dan Matematika, 2025)
In the 21st century, mathematical literacy skills are among the most crucial competencies for students. However, current levels of student proficiency in this area remain suboptimal. This study aims to develop REACT strategy teaching materials that incorporate Islamic context mathematical literacy questions on the topic of algebraic function limits. The development model used in this study is the ADDIE model, which comprises five stages: Analyze, Design, Development, Implementation, and Evaluation. The test subjects in this study included expert validators consisting of three mathematics education lecturers from UIN Syarif Hidayatullah Jakarta, five high school mathematics teachers, and one high school Islamic religion teacher. Additionally, a limited trial was conducted with 30 grade XII MIPA students at SMA Muhammadiyah Sawangan. The instruments used in this study included expert validation instruments, student response questionnaires, and Islamic context mathematical literacy ability tests. The results indicated that the REACT strategy teaching materials developed achieved a high level of validity, with a validation score of 0.89 from expert evaluators. The level of practicality was also high, with a score of 0.93, indicating very feasible criteria based on student response questionnaires. The developed teaching materials were considered effective in facilitating mathematical literacy skills in the Islamic context, based on an average test of student learning outcomes against the Minimum Competency Standards - Kriteria Ketuntasan Minimal (KKM), with a student success rate of 63%. The conclusion of this study is that the REACT strategy teaching materials designed to enhance students' mathematical literacy skills in the Islamic context, specifically on the topic of function limits, have met the quality standards for teaching materials in terms of validity, practicality, and effectiveness, making them suitable for classroom use.